Two-point discrimination and kinesthetic sense disorders in productive age individuals with carpal tunnel syndrome - Wolny, Tomasz (J Occup Health, 2016)
OBJECTIVES: The aim of this study was to evaluate two-point discrimination (2PD) sense and kinesthetic sense dysfunctions in carpal tunnel syndrome (CTS) patients compared with a healthy group. METHODS: The 2PD sense, muscle force, and kinesthetic differentiation (KD) of strength; the range of motion in radiocarpal articulation; and KD of motion were assessed. RESULTS: The 2PD sense assessment showed significantly higher values in all the examined fingers in the CTS group than in those in the healthy group (p<0.01). There was a significant difference in the percentage value of error in KD of pincer and cylindrical grip (p<0.01) as well as in KD of flexion and extension movement in the radiocarpal articulation (p<0.01) between the studied groups. CONCLUSIONS: There are significant differences in the 2PD sense and KD of strength and movement between CTS patients compared with healthy individuals.